Daniela Serna: From the Expanding Text to the Limits of Shape (2020)
Daniela Serna (Medellín, 1991) conducts research and creates works of art on the transition between a literary verbal object and a visual artifact of a plastic and esthetic nature. Her work expands on the idea of formal literature, where the temporal and sensorial dimensions are in the reader’s imagination, to propose visual poems that encourage an experience of meaning that augments or blurs the limits of what is possible. This review deals with a set of works, the core topic of which enables multiple readings, which are carefully selected using a collection of ideological, political, and esthetic signs that the artist brings into her work and that allow us to question the relationship between the represented fictional world and the reader or observer’s representation.